Development of Environmental Pollution E-Module Containing Socio Scientific Issue to Train Students' Scientific Literacy - Fitriani, Rizki (Universitas Negeri Semarang, 2023)
This study aims to analyze the characteristics, validity, readability of the E-module and the profile of students' scientific literacy after using the E-module. The design of this research is Research and Development (R&D), using the Sugiyono development model which consists of ten steps, potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials, product revisions, and mass production. The research subjects were VII grade students of SMP N 10 Magelang. The average score by the media validator is 96.25% very valid criteria and the material validator is 94.16% very valid criteria. The average score of the small-scale readability test is 91.60% and the average on the large-scale is 92.50% very good category. Based on the results of student scientific literacy profil 6.25% students are in the low scientific literacy, 13% students are in the medium category, 56.25% students are in the high category and 25% students are in the very high category . Based on the results of the study, it can be concluded that the environmental pollution E-module containing the Socio Scientific Issue is valid for use in science learning and can train students' scientific literacy skill.